EFFECTIVE METHODS OF IMPROVING SPEAKING SKILLS IN ENGLISH LANGUAGE LEARNING - Ashuraliyeva Laylo, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes effective methods for improving speaking skills in English language learning. In the context of globalization, the ability to speak English fluently and confidently has become one of the most important competencies in modern education. The article examines various approaches to developing speaking skills, including the communicative approach, creating an immersive language environment, role-playing activities, pair and group work, the use of audio-visual materials, and modern digital learning platforms.